Harnessing wood bottom ash for efficient arsenic removal from wastewater: Adsorption mechanisms and process optimisation - Lee, Jae In; Jeong, Yohan; Lee, Youn Jun; Lee, Chang Gu; Park, Seong Jik (Chemosphere, 2024)
This study explored the innovative application of wood bottom ash (WBA) as an adsorbent for arsenic (As) removal from wastewater, focusing on the adsorption mechanism and optimisation of the operational conditions. Comprehensive spectroscopic analyses, including FE-SEM/EDS, BET, XRF, XRD, FT-IR, and XPS, were performed to examine the elemental and mineralogical changes in WBA before and after As adsorption. The study assessed the adsorption kinetics and isotherms, revealing that As adsorption reached equilibrium within 48 h, with a maximum capacity of 121.13 mg/g. The adsorption process followed a pseudo-second-order kinetic model and aligned well with the Langmuir isotherm, indicating that the process is governed by chemisorption and occurs as monolayer adsorption. The primary removal mechanism was the surface precipitation of amorphous calcium arsenate. Response surface methodology was employed to analyse and optimise the factors influencing As removal, including solution pH, ionic strength, adsorbent dose and reaction time. The optimal conditions for maximum As removal were pH 7.11, 8.37 mM ionic strength, 9.08 g/L WBA dose, and 2.58 h reaction time. This study offers novel insights into the efficient and cost-effective use of WBA for As removal, highlighting its potential as a sustainable solution for wastewater treatment in developing countries.
Keywords: Adsorption mechanism; Adsorption process; Adsorption properties; Arsenic adsorption; Arsenic removal; Bottom ash; Calcium arsenate; Mechanism optimization; Response-surface methodology; Solution pH; Adsorption; Arsenic; Coal Ash; Hydrogen-Ion Concentration; Kinetics; Osmolar Concentration; Spectroscopy, Fourier Transform Infrared; Waste Disposal, Fluid; Wastewater; Water Pollutants, Chemical; Water Purification; Wood; Adsorption properties; Calcium arsenate; Ionic strength; Response surface methodology; Solution pH